2017
DOI: 10.1016/s2214-109x(17)30135-3
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and early outcomes of cervical cancer patients at Butaro District Hospital, Rwanda: a retrospective review

Abstract: Background Cancer treatment facilities are scarce in rural areas of low-income and middle-income countries, where the highest burden of cervical cancer exists. The Butaro Cancer Center of Excellence (BCCOE), in rural Rwanda, is a Rwandan Ministry of Health facility supported by Partners In Health and Dana-Farber/Brigham and Women's Cancer Center. The cervical cancer programme includes diagnosis, staging, and treatment. However, because of resource limitations, only 15 patients per month could be referred for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Currently, Rwanda has no national cervical cancer screening program. A study performed at Butaro Cancer Center in Rwanda showed that 97% of cervical cancer patients enrolled from July 2012 to June 2015 had stage II disease or above ( Davey et al, 2017 ). Delay in diagnosis is a major concern in cervical cancer control, with both patients and healthcare providers contributing to these delays ( Gyenwali et al, 2014 , Zeleke et al, 2021 , Behnamfar and Azadehrah, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, Rwanda has no national cervical cancer screening program. A study performed at Butaro Cancer Center in Rwanda showed that 97% of cervical cancer patients enrolled from July 2012 to June 2015 had stage II disease or above ( Davey et al, 2017 ). Delay in diagnosis is a major concern in cervical cancer control, with both patients and healthcare providers contributing to these delays ( Gyenwali et al, 2014 , Zeleke et al, 2021 , Behnamfar and Azadehrah, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Screening is opportunistic and typically provided per patient request. As there are no clinics dedicated solely to cervical cancer screening, most patients diagnosed with cervical cancer are evaluated because they are symptomatic, accounting for the large percentage of cervical cancer patients diagnosed at an advanced stage ( Davey et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The high mortality rate associated with cervical cancer in Rwanda is, in part, due to late diagnosis of the disease. A study done at Butaro Cancer Center in Rwanda showed that 97% of cervical cancer patients enrolled at the center from July 2012 to June 2015 had stage II disease or above (7). Delay in diagnosis is a major concern in cervical cancer prevention and treatment programs.…”
Section: Introductionmentioning
confidence: 99%